Inovasi, Angka Kelahiran Perusahaan Serta Pengaruh Moderasi Aplikasi Paten - Onny Setiawan; Okalesa Okalesa; Sarli Rahman; Ienne Yoseria Putri (COSTING : Journal of Economic, Business and Accounting, 2020)
ABSTRACT Innovation is the foundation of a company's life. The purpose of this study is to understand the effect of innovation on the birth rate of enterprises by using macro data in a country. Data on the birth rate of a company is used to see the effectiveness of a country's innovation in increasing the number of entrepreneurs in its country. The results showed that of the 16 OECD member countries that became the study sample it was found that the innovation activities undertaken by these countries, especially R&D activities, were not proven to be effective and applicable in creating new businesses. Meanwhile, the patent application only helps in terms of changing the direction of its influence, which was negative to positive initially, but not proven statistically significant. Keyword : Innovation, R&D Expenditure, Number of Patent Applications, Birth Rate of Enterprises, OECD.